Effect of Cell Density Changes and Conditioned Media on Carrot Cell Embryogenesis - Hari, V.
The effect of cell population density and of conditioned media on embryogenesis showed that one particular cell line of carrot showed a linear relationship between cell density and total number of embryos produced at all concentrations tested. However, another cell line produced a lower than expected number of embryos at low cell densities. At all cell densities the presence of conditioned media increased total number of embryos produced and the rate of development was also accelerated.
Keywords: DAUCUS CAROTA; CELL DENSITY; CONDITIONED MEDIA; EMBRYOGENESIS